Advocating Community Support for Exclusive Breastfeeding for Women Workers: A Critical Review - Fitriyani Sukamto, Dhita Nur; Basrowi, Ray Wagiu (Ridwan Institute, 2023)
With the increasing participation of women in the workforce, the dynamics of motherhood, especially for mothers who breastfeed, have undergone significant changes. These changes have had considerable implications, prompting an exploration of the challenges and advantages women workers face to balance breastfeeding and their professional commitments. This comprehensive review delves into complex views on breastfeeding among working women. The main objective is to explain the benefits, barriers, and relevant strategies related to breastfeeding in the workplace, with the aim of providing insight into forming an effective support system. The benefits of breastfeeding while working, including decreased absenteeism, increased productivity, and decreased worker turnover rates, are powerful incentives. However, various challenges hinder this practice, including inadequate research, inadequate support on the part of employers, logistical problems such as distance between home and workplace, lack of lactation facilities in the workplace, and decreased milk production during working hours. The discussion emphasized the need for a strong lactation promotion model, consisting of seven essential components, tailored to strengthen breastfeeding support in the workplace environment. To facilitate successful breastfeeding for working mothers, it is recommended to provide options such as part-time work or early return for mothers with babies under six months, coupled with important company provisions such as dedicated lactation support staff, educational materials, and peer groups, which are crucial. The integration of occupational physicians in the proposed lactation promotion is an important step toward achieving high breastfeeding rates among female workers.